2005
DOI: 10.1095/biolreprod.105.039719
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Epididymal Transcriptome: Transcriptional Profiling of Segmental Gene Expression in the Epididymis1

Abstract: Maturation of spermatozoa, including the acquisition of motility and the ability to undergo capacitation, occurs during transit through the dynamic environment of the epididymis. The microenvironments created along the length of the epididymal tubule are essential to the molecular modifications of spermatozoa that result in fertile gametes. The secretory and resorptive processes of the epithelial cells that line this tubule generate these microenvironments. In the current study, 10 morphologically distinct seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
232
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(269 citation statements)
references
References 19 publications
16
232
2
1
Order By: Relevance
“…Our data indicate that these proteins are expressed in a spatiotemporally exclusive pattern that is nearly parallel to that reported for the corresponding mRNAs using a large-scale expression profiling method and deposited at http://mrg.gs.washington.edu/cgibin (Johnston et al, 2005). …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our data indicate that these proteins are expressed in a spatiotemporally exclusive pattern that is nearly parallel to that reported for the corresponding mRNAs using a large-scale expression profiling method and deposited at http://mrg.gs.washington.edu/cgibin (Johnston et al, 2005). …”
Section: Discussionsupporting
confidence: 72%
“…Recent studies have identified dynamic gene expression patterns along the mouse, rat and human epididymal segments and many genes including cell cycle regulators show segment specific expression pattern (Dube et al, 2007;Jelinsky et al, 2007;Johnston et al, 2005;Turner et al, 2007a). However, it is unknown if similar expression patterns occur in parallel in the corresponding proteins encoded by these genes in various segments.…”
Section: Introductionmentioning
confidence: 99%
“…16 Dysfunction of RB1 is associated with many human cancers. 17 Rb1 RNA is expressed in the mouse, 18 rat 19 and human epididymis. 20 The expression of the tumour suppressor genes Pten and Rb1 counter-balances the activity of pro-proliferative signal proteins in the proximal epididymis of mice.…”
Section: Epididymal Cancer Progenitor Cellsmentioning
confidence: 99%
“…The expression of K-Ras, B-Raf and Myc, expressed in the adult human epididymis, 20 enhances the basal expression of the transcription factor Nrf2 (nuclear factor E2-related factor 2), which controls intracellular levels of ROS through an inducible antioxidant programme. 47 Nfe2l2 (Nrf2) mRNA is highly expressed throughout the rat 19 and mouse epididymis 18 and also found in that of man. 20 Adult Nrf2 2/2 male mice suffer reduced antioxidants and raised lipid peroxidation in the epididymis, accompanied by reduced epididymal sperm motility.…”
Section: Endogenous Protection Against Mutagenic Microenvironmentsmentioning
confidence: 99%
“…Once the spermatozoon is released to the lumen, it travels through rete testis and epididymis. There, it is confronted to a complex and specific microenvironment, which varies along the epididymis (Johnston et al 2005, Sullivan et al 2005. This complex fluid interacts with the sperm surface and induces its acquisition of motility and fertilizing abilities (Orgebin-Crist 1967, Zhou et al 2004.…”
Section: Introductionmentioning
confidence: 99%